Perancangan Purwarupa Sistem Pemantauan dan Pelaporan Proses Pembelajaran dalam Kurikulum Merdeka Berbasis Aplikasi Web di Sekolah Binekas - Septiawan, Reza Rendian; Nasution, Surya Michrandi; Ruriawan, Muhammad Faris (Jurnal Pengembangan dan Pengabdian Masyarakat Multikultural, 2025)
The Kurikulum Merdeka emphasizes essential content and fundamental concepts, designed with flexibility to enable adoption and tailored implementation across educational institutions while ensuring alignment with the established Learning Outcomes (Capaian Pembelajaran; CP). However, this flexibility and its differentiated learning approach, which caters to the unique abilities of each student, pose challenges for educators, requiring them to closely monitor the delivery of material and its alignment with the defined Learning Outcomes. Sekolah Binekas, a prestigious private institution in South Bandung, currently relies on manual methods for preparing and reporting learning activities using either physical documents or digital files. This approach complicates the process of tracking and monitoring learning outcomes. To address this issue, a system is needed to streamline the archiving of planning documents and the reporting of learning activities, enabling more efficient monitoring of CP. As part of this initiative, a web-based prototype system has been successfully developed to assist Sekolah Binekas in the daily reporting and monitoring of learning activities. Its accessibility for educators ensures ease of use, and if proven effective, the system could serve as a model for implementation in other schools.